Implicações do pronto-atendimento psicológico de emergência aos que vivenciam perdas significativas - SOUZA, Airle Miranda de (2016)
The proposal of this work consisted in presenting a service of psychological attendance to the ones who are experiencing a significant loss, be it by the death of a person of a significant relationship, as a familiar or a friend, the death of a pacient or the loss of health at the time of hospitalization, within others, and the results of such service were discussed. The methodological focus was based in the analysys over the structuration process and the implantation of a service of this specialty in a public college hospital, where the authors developed the assistance to the ones who experience this kind of loss. The results showed the importance of this service, which was demanded not only by the ones who experience loss of health or death of a significant person but also by education and health professionals.